Prevalence of obesity in school children aged 11-15 years in western district of Tamil Nadu - Dr. Suganthi.V; Dr. Arunthathi. A; Dr. Nayana. T (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Obesity in children and adolescents is an important public health problem in India. This study was done to estimate the prevalence of obesity in 11-15 years urban school children using Body mass index. (BMI), waist circumference (wc), waist height ratio (WHtR) and to determine the screen viewing time – arisk factor for obesity.Methods: This was a descriptive cross-sectional study. It was conducted over 12 months in the year 2014 in 11- 15 years urban school children in Coimbatore district. About 859 children were selected for this study. A proforma was used to collect the details such as age, gender, type of school, screen viewing time. Weight, height, waist circumference of these children was measured and prevalence of obesity was estimated based on the 3 indices- BMI, WC, WHtR. The data were analyzed with a statistical software package.Results: Out of the 859 children, the sample strata was 170 for each age group from 11-15 years. About 5% were obese by BMI, 18 % by WC, 14% by WHtR. The prevalence in females was 7% (BMI), 22% (WC), 17% (WHtR) and in males it was 1%(BMI), 10%(WC), 7%(WHtR). The prevalence of obesity in private schools was 10%. (BMI), 21%(WC), 16% (WHtR) and in government schools, it was 3% (BMI), 9% (WC), 7%(WHtR). The prevalence in screen viewing time less than 2 hours was 3%(BMI), 9%(WC),12%( WHtR), and in more than 2 hours it was 10% (BMI), 20% (WC), 23% (WHtR).Conclusion: The prevalence of obesity in high school children according to BMI is 5%., WC 18% and WHtR 14%. It is more in females, children studying in private schools and in those with screen viewing time more than 2 hours.